Absolving God's Laws: Thomas Hobbes's Scriptural Strategies. (October 2022) - McQueen, Alison
Thomas Hobbes tells us that he wrote Leviathan to "absolve the divine laws" of the charge that they justify rebellion. This article interprets the argumentative strategy of the second half of Leviathan in light of this intention. Over the course of his three major political works, Hobbes develops a convergent argument to absolve God's laws. This strategy of judicial rhetoric relies on using multiple independent claims in the hope that one's audience finds at least one of them persuasive. This was a risky strategy for Hobbes that angered his critics. The strategy also reveals something about what sort of philosopher Hobbes was and how we ought to approach his work.